Machine learning on alluvial deposit Identification in dryland area - Vio, Daniel; Jonas Otaviano Praça de Souza; Gustavo Henrique Matos Bezerra Motta; Leandro Carlos de Souza (Revista Contexto Geográfico, 2025)
There is a growing global concern about water resources and an increasing interest in studies identifying groundwater. Alluvial aquifers exhibit varied forms and irregular distribution in the landscape, making their location challenging. This study applies machine learning (ML) techniques to detect alluvial deposits in the Riacho do Tigre watershed in the semi-arid region of northeastern Brazil. Fourteen input variables and one output variable were collected across approximately one and a half million points distributed along the main channels of the watershed. Using decision trees (DT), the model was trained and validated through k-fold cross-validation and bootstrap methods, achieving an accuracy of 0.916, indicating good performance in classifying alluvial areas.